Upaya meningkatkan kemampuan siswa dalam mengoperasionalkan penjumlahan dan pengurangan pada mata pelajaran matematika dengan bantuan benda konkret di kelas I sekolah dasar - Kastirah, Kastirah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
Education is a human effort to prepare themselves for their role in the future. The teaching and learning process is the core of the overall educational process with the teacher as the main role holder. To improve students' mastery and understanding of the subject matter, the teacher tries to use concrete media objects obtained around the school environment in operating the addition and subtraction of numbers. The approach used in this study is a qualitative approach, namely describing the actual problems in the field, then reflecting and analyzing them based on supporting theory followed by implementing actions in the field. Classroom action research was conducted in two cycles. each cycle begins with planning the application of action and observation, and ends with reflection. it can be concluded that: (1) The evaluation value of Silkus I and Cycle II has increased; (2) With the aid of concrete objects students can operationalize addition and subtraction of numbers; (3) the standard of graduation is achieved; (4) Learning to use visual aids in the form of concrete objects properly and correctly can arouse students' interest in learning so that learning actions in cycles I and II can be achieved.